Study on the Optical Field Distribution of Asymmetric Nanostructures Based on Surface Plasmon - Leijun Zhang; Jiao Jiao; Jisheng Tong; Chunguang Ma; Qing Zhao (IEEE Photonics Journal, 2019)
Optical force, which is known as a powerful effect of the light on all objects and is too weak to be perceived directly. While the momentum transfer between light and matter can be greatly improved at the nanometer scale. In this paper, we mainly designed an asymmetric deep subwavelength metal nanostructure to generate a strong optical field gradient force by utilizing the resonant interaction between light and nanostructures as well as coupled excitation of surface plasmon, which can promote the movement of the nanoparticles. After simulating and optimizing, we learned that the intensity of optical field excited by the stepped trapezoidal nanostructure we designed in this paper is 140 times higher than that of incident light. At last, we fabricated and tested the sample of the designed nanostructures with the method of electron-beam lithography (EBL), and get the data of the speckle distribution curve and scattering curve of the sample. We discovered that in the wavelength range from 300 nm to 1100 nm, the sample will be excited to a strong plasma. It can be inferred that the devices cascaded by such structural units can accelerate and emit a large number of nanoparticles to generate considerable thrust, which has a great application prospects for the precise positioning of spacecraft.